1994
DOI: 10.1111/j.1754-4505.1994.tb01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of orthodontic anomalies in mentally retarded developmentally disabled (MRDD) persons

Abstract: For this epidemiologic study, 458 individuals with mental retardation and developmental disability (MRDD), from 6 to 87 years old, from the Lower Hudson Valley region of New York, were evaluated for the occurrence of orthodontic anomalies. High occurrence of both anomalies of intermaxillary relation, as determined by Angle's classification, and the anomalies of occlusion were found in these individuals when compared with the general population. An increased incidence of both acquired (i.e., open bite) as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 4 publications
6
47
3
3
Order By: Relevance
“…This is in agreement with a study that reported an increase incidence of Angle class III malocclusion in children with DS. 16 On the contrary, the study did not conform to previous study where it was reported that AD children had higher incidence of class II and III malocclusion. 16 The majority of the DS and AD children had 2 mm overjet and also 20% overbite.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This is in agreement with a study that reported an increase incidence of Angle class III malocclusion in children with DS. 16 On the contrary, the study did not conform to previous study where it was reported that AD children had higher incidence of class II and III malocclusion. 16 The majority of the DS and AD children had 2 mm overjet and also 20% overbite.…”
Section: Discussioncontrasting
confidence: 56%
“…16 On the contrary, the study did not conform to previous study where it was reported that AD children had higher incidence of class II and III malocclusion. 16 The majority of the DS and AD children had 2 mm overjet and also 20% overbite. The prevalence of posterior right and left cross bite was highly prevalent in the DS group compared with the AD group.…”
Section: Discussioncontrasting
confidence: 56%
“…Este grupo de niños, realizan la masticación mayoritariamente con movimiento de bisagra, no existiendo una molienda real, razón por la cual se alimentan con consistencia picado o molido con tenedor. Coincidimos con otras investigaciones en relación a que los factores determinantes no están muy claros, pero pueden ser una asociación de alteración en el tono muscular, falta de actividad oral, retardo mental, falta de madurez psicomotora, disfunción respiratoria, lingual u oclusal o falta de estímulo por parte de los padres [13][14][15] . Si bien los hábitos de succión no mostraron ser significativos en el desarrollo de ADM, es importante notar que están presentes en 56,9% de los niños que no tienen lateralidad, en 59% de los niños con incompetencia labial, en 54,4% de los niños dolicofaciales y en 30% de los pacientes con mordida abierta.…”
unclassified
“…Age and social-cultural differences of the studied population as well as the variations in malocclusion classification and diagnostic criteria or indices used by researchers account for the big range of malocclusion reported worldwide [11,12]. In contrary, the type of disability is the main reason for disparities of reported malocclusion prevalence among handicapped people [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Vittek et al, [13] and Viglid [8] reported more than 90% prevalence of malocclusions among subjects with cerebral palsy and Down's syndrome, respectively. Nonetheless, the reported prevalence of malocclusion for sensory and physically disabled subjects ranges from 27 to 58 percent [9,14].…”
Section: Introductionmentioning
confidence: 99%